Pastoral development in the Sahel - Greenwood, Gregory Boyce, author; Bartlett, E. T., advisor; Alers-Montalvo, Manuel, committee member; Wasser, Clinton, committee member (Colorado State University. Libraries, 1980)
Ecological, geographic, economic and anthropological literature pertaining to the Sahel is reviewed in order to provide a basis for pastoral development policy. Great variability in annual primary production is the principal characteristic of Sahelian vegetation. The range can best be improved by increasing the density of woody plants on dry season range. Simple grazing trials are recommended to verify and quantify this improvement. Traditional pastoral systems were found to be well adapted to the great variability of the Sahel. Traditional strategies sought to obtain a consummable output while maintaining a level of risk aversion. The role of commercialization in an optimal strategy is unclear and may depend on the pastoralist's wealth, personal discount rate, perception of future risk and perception of his herd as a risk averting mechanism. Historical events have increased pressure on the resource base while disrupting the traditional social and political structures of the Sahel. Resource degradation and increased household insecurity have resulted. Development projects must change the micro-economic environment of the pastoralist by simultaneously increasing primary production and decreasing risk. A number of ecological and social techniques are discussed. A new type of rural institution is proposed that would unite pastoralists, local government officials and technical experts in developing, testing and evaluating potential solutions.
Keywords: Pastures -- Research -- Sahel; Pasture ecology -- Sahel